A rare endocrinological complication of chronic kidney disease - Çamlar, Seçil Arslansoyu; Filibeli, Berna; Soyaltın, Eren; Manyas, Hayrullah; Çatlı, Gönül; Alaygut, Demet; Mutlubaş, Fatma; Dündar, Bumin Nuri; Demir, Belde Kasap (The Turkish Journal of Pediatrics, 2022)
Background. Chronic kidney disease (CKD) may lead to increase in serum levels of peptide hormones as a result of changes in peripheral metabolism. The pathogenesis of uremic hyperprolactinemia in CKD is not fully understood. Plasma prolactin levels are elevated in women, pubertal girls, and also in men with chronic kidney disease. But this is not comon in prepubertal boys. Also in prepubertal children and postmenopausal women, hyperprolactinemia rarely results in galactorrhea. We aimed to discuss hyperprolactinemia and galactorrhea in a 12-year-old male with CKD. Case. A twelve-year-old boy with chronic kidney disease (CKD) suffered from bilateral galactorrhea. He was on follow-up at Pediatric Nephrology Department from the age of two due to bilateral dysplastic kidney. On physical examination, his weight was - 0.59 SDS, height was -2.82 SDS, Blood pressure was 115 / 72 (75p), stretched penis length was 6 cm, testicular volume was 3mL / 3mL, pubic hair was Tanner Stage 1, breast examination did not reveal plaque on bilateral breast. He was receiving recombinant erythropoietin, sodium bicarbonate, polystyrene sulfonate, calcium acetate, and calcitriol treatments. Glomerular filtration rate was 23ml/min/1.73 m2 (CKD stage IV). Serum prolactin (PRL) was > 200 μg/L (N, 2.64-13.13). The pituitary adenoma was excluded with pituitary and cranial magnetic resonance imaging (gadolinium). Cabergoline (0.5 mg/ twice weekly) was initiated to decrease PRL levels and reduce galactorrhea. In the second week of treatment, serum PRL level was suppressed (0.4 μg/L) and galactorrhea was completely resolved. Conclusions. Although uremic hyperprolactinemia is very rarely seen in childhood, it is important to evaluate, and initiate an appropriate treatment since it is associated with delayed puberty and infertility in adulthood in many cases.